Intramuscular anabolic signaling and endocrine response following resistance exercise: Implications for muscle hypertrophy - Gonzalez, A. M.; Hoffman, J. R.; Stout, J. R.; Fukuda, D. H.; Willoughby, D. S. (Sports Medicine, 2016)
Maintaining skeletal muscle mass and function is critical for disease prevention, mobility and quality of life, and whole-body metabolism. Resistance exercise is known to be a major regulator for promoting muscle protein synthesis and muscle mass accretion. Manipulation of exercise intensity, volume, and rest elicit specific muscular adaptations that can maximize the magnitude of muscle growth. The stimulus of muscle contraction that occurs during differing intensities of resistance exercise results in varying biochemical responses regulating the rate of protein synthesis, known as mechanotransduction. At the cellular level, skeletal muscle adaptation appears to be the result of the cumulative effects of transient changes in gene expression following acute bouts of exercise. Thus, maximizing the resistance exercise-induced anabolic response produces the greatest potential for hypertrophic adaptation with training. The mechanisms involved in converting mechanical signals into the molecular events that control muscle growth are not completely understood; however, skeletal muscle protein synthesis appears to be regulated by the multi-protein phosphorylation cascade, mTORC1 (mammalian/mechanistic target of rapamycin complex 1). The purpose of this review is to examine the physiological response to resistance exercise, with particular emphasis on the endocrine response and intramuscular anabolic signaling through mTORC1. It appears that resistance exercise protocols that maximize muscle fiber recruitment, time-under-tension, and metabolic stress will contribute to maximizing intramuscular anabolic signaling; however, the resistance exercise parameters for maximizing the anabolic response remain unclear.